Relative abundance of insect pests and their predators on boro rice (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted to know the relative abundance of insect pests and their predators on 5 boro rice varieties namely Arize tez, Teea, Sakti, Sathi and BRRI Dhan 28. In Arize Tez variety, short horned grasshopper revealed the highest percent relative abundance (87.25%) at tillering stage and green rice leafhopper was only at panical initiation stage. Among insect predators, wasp showed the highest percent relative abundance (33.33%) both at tillering and panical initiation stages. In Teea variety, the highest percent relative abundance of short horned grasshopper was recorded at tillering (80.21%) and panicle initiation (86.03%) stages while spider and lady bird beetle had 21.05% at tillering stage, wasp (21.05% and 40.00%), damselfly (21.05% and 40.00%) at tillering and panical initiation stages, respectively. In Sakti variety, short horned grasshopper had the highest percent relative abundance (72.54% and 69.05%) at tillering and panicle initiation stages while dragonfly had 30.77% at tillering, wasp had 30.77% and 66.66% at tillering and panicle initiation stages. In Shathi variety, the highest percent relative abundance of short horned grasshopper was recorded at tillering (59.46%) and panicle initiation (52.27%) stages while wasp (41.67%) at panical initiation stage. In variety BRRI dhan 28, the highest percent relative abundance of insect pests was recorded in short horned grasshopper (76.73% and 86.05%) both at tillering and panicle initiation stages while in insect predators, wasp had 40% at tillering and 50% at panicle initiation stages but dragonfly had 50% only at panicle initiation stage.Bangladesh J. Agril. Res. 43(1): 81-88, March 2018